Frost resistance of seeds in Mediterranean oaks and the role of litter - Esteso-Martínez, Jordán; Gil-Pelegrín, Eustaquio (Ann. For. Sci., 2004)
The endogenous frost resistance of the seeds of four Mediterranean oaks (Quercus coccifera, Q. faginea, Q. ilex and Q. pyrenaica) with different leaf abscission phenology was tested. Thermal analysis and polyelectrolytes leakage methodologies were employed to establish lethal temperature thresholds. Results showed a higher frost resistance for evergreen species and lower for deciduous species in this decreasing order: Q. coccifera, Q. ilex, Q. faginea and Q. pyrenaica. The cover of leaf litter generated by deciduous species could be an isolating element which allowed seed survival under cold winter conditions to that species with a lower frost resistance. Differences in temperature above and below a leaf litter cover along a winter season were measured in a Q. faginea stand, in this sense the kind effect of leaf litter from a thermal point of view was proved.
Keywords: frost resistance; leaf litter; polyelectrolytic leakage; Quercus; thermal analysis

Frost resistance of seeds in Mediterranean oaks and the role of litter - Esteso-Martínez, Jordán; Gil-Pelegrín, Eustaquio (Ann. For. Sci., 2004)
The endogenous frost resistance of the seeds of four Mediterranean oaks (Quercus coccifera, Q. faginea, Q. ilex and Q. pyrenaica) with different leaf abscission phenology was tested. Thermal analysis and polyelectrolytes leakage methodologies were employed to establish lethal temperature thresholds. Results showed a higher frost resistance for evergreen species and lower for deciduous species in this decreasing order: Q. coccifera, Q. ilex, Q. faginea and Q. pyrenaica. The cover of leaf litter generated by deciduous species could be an isolating element which allowed seed survival under cold winter conditions to that species with a lower frost resistance. Differences in temperature above and below a leaf litter cover along a winter season were measured in a Q. faginea stand, in this sense the kind effect of leaf litter from a thermal point of view was proved.
Keywords: frost resistance; leaf litter; polyelectrolytic leakage; Quercus; thermal analysis

Feeding preferences of the collembolan Onychiurus sinensis for fungi colonizing holm oak litter ( Quercus rotundifolia Lam.) - Sadaka-Laulan, N; Ponge, J F (European Journal of Soil Biology, 1998)
Ten fungi isolated from decaying holm oak leaves (Quercus rotundifolia Lam.) have been presented to the collembolan species Onychiurus sinensis (Hexapoda). The attractiveness and selectivity of the ten fungi was investigated taken into account the effect of the substrate on which the fungus was growing (malt-agar or litter) and the effect of fungal odour. Furthermore, moulting, growth, survival and reproduction of 0. sinensis in the presence of each of the ten test fungi were studied. Mucor plumbeus and Trichothecium roseum were the most preferred whatever the culture substrate and their odour was the most attractive. Two fungi (Penicillium spinulosum and the Basidiomycete S41) attracted Collembola by their odour but were not preferred as food sources. The animals could survive and reproduce on a mono-diet of several of our test fungi, but not on the Basidiomycete S41 and on Trichoderma polysporum.
Keywords: Collembola; feeding preferences; fungal odour; fungi; leaf litter

Long-term CO 2-enrichment in a Mediterranean natural forest: An application of large Open Top Chambers - Angelis, P De; Scarascia-Mugnozza, G E (Chemosphere, 1998)
It is crucial to be able to anticipate the possible effects of environmental changes on the Mediterranean woodland communities given their essential role on protecting lands that are under a strong pressure by man and climate. Predictions of the effects of increasing C0~ concentration on plants have been inferred by short- and long-term studies, conducted at different scales and by different technologies. Open Top Chambers (OTCs) are experimental facilities that have been widely used to expose field grown plants to different pollutant gases, and more recently to elevated [CO2] . In this paper, we present the natural site and the experimental system (six large OTCs enclosing clumps of natural vegetation) that we have been utilizing for 3 years, to assess the impact of elevated [CO2] on a Mediterranean natural forest community. The results show that large OTCs can be usefully used to simulate C02 doubling even under the harsh environmental conditions of the mediteffanean region
Keywords: decomposition; Elevated CO3; leaf litter; Mediterranean forest (voyant)

Long-term CO 2-enrichment in a Mediterranean natural forest: An application of large Open Top Chambers - Angelis, P. De; Scarascia-Mugnozza, G. E. (Chemosphere, 1998)
It is crucial to be able to anticipate the possible effects of environmental changes on the Mediterranean woodland communities given their essential role on protecting lands that are under a strong pressure by man and climate. Predictions of the effects of increasing C0~ concentration on plants have been inferred by short- and long-term studies, conducted at different scales and by different technologies. Open Top Chambers (OTCs) are experimental facilities that have been widely used to expose field grown plants to different pollutant gases, and more recently to elevated [CO2] . In this paper, we present the natural site and the experimental system (six large OTCs enclosing clumps of natural vegetation) that we have been utilizing for 3 years, to assess the impact of elevated [CO2] on a Mediterranean natural forest community. The results show that large OTCs can be usefully used to simulate C02 doubling even under the harsh environmental conditions of the mediteffanean region
Keywords: decomposition; Elevated CO3; leaf litter; Mediterranean forest (voyant)

Growth inhibition of nematophagous and entomopathogenic fungi by leaf litter and soil containing phenols - Lopez-Llorca, L V; Olivares-Bernabeu, C (Mycological Research, 1997)
In a soil survey, nematophagous fungi were recovered less from agar plates sprinkled with forest soil (Quercus ilex subsp. rotundifolia) than from those incubated with agricultural (Citrus orchards) soil. Nematodes were present in all soils. The organic matter was higher in forest soils. Water extracts from forest soils with high levels of phenols, leaf litter and Q. rotundifolia fresh leaves aﬀected the development and growth of common species of nematophagous and entomopathogenic fungi. These results show that phenolics from leaf letter could play an important role in the ecology and biology of these invertebrate pathogens in soil.
Keywords: agricultural soil; entomopathogenic fungi; forest soil; fungal growth (voyant); leaf litter; nematophagous fungi; phenolic compounds; quercus ilex ssp rotundifolia

Growth inhibition of nematophagous and entomopathogenic fungi by leaf litter and soil containing phenols - Lopez-Llorca, L. V.; Olivares-Bernabeu, C. (Mycological Research, 1997)
In a soil survey, nematophagous fungi were recovered less from agar plates sprinkled with forest soil (Quercus ilex subsp. rotundifolia) than from those incubated with agricultural (Citrus orchards) soil. Nematodes were present in all soils. The organic matter was higher in forest soils. Water extracts from forest soils with high levels of phenols, leaf litter and Q. rotundifolia fresh leaves aﬀected the development and growth of common species of nematophagous and entomopathogenic fungi. These results show that phenolics from leaf letter could play an important role in the ecology and biology of these invertebrate pathogens in soil.
Keywords: agricultural soil; entomopathogenic fungi; forest soil; fungal growth (voyant); leaf litter; nematophagous fungi; phenolic compounds; quercus ilex ssp rotundifolia

Decomposition of mediterranean leaf litters: A microcosm experiment investigating relationships between decomposition rates and litter quality - Cortez, J; Demard, J M; Bottner, P; Jocteur Monrozier, L (Soil Biology and Biochemistry, 1996)
he decomposition of four mediterranean species leaf litter (Sessile oak, Quercus petraea L.; Holm oak, Quercus ibex L.; Sweet chestnut, Castanea satiua Mill and beech, Fagus syluatica L.) was studied for 90 days under controlled conditions. Respiration and litter mass loss were measured in three types of microcosms: (1) Soil only; (2) Soil + l-y old litter and (3) Soil + l-y old litter + newly senescent litter (freshly fallen). Variations in chemical composition of the litters were determined before and after incubation by the pyroanalysis method. For newly senescent litters decomposition rates per day Kco, (calculated from CO, release) and K, (calculated from mass losses) fitted to the first order exponential decay decreased as follows: sessile oak (Kc,_,, = 0.0043; K, = 0.0049) > holm oak (Km, = 0.0031; K, = 0.0040) = beech (&o~ = 0.0030; K, = 0.0030) > sweet chestnut (Kc% = 0.0001; K,, = non- significant regression); For l-y old litters sweet chestnut (Ko,, = O.oo40, K, = 0.0065) > sessile oak (KEO, = 0.0035; K, = 0.0039) > beech (Kcc,, = 0.0030; K, = non-significant regression). All litters showed a reduction of lipid (mean loss 90.5%), hydrosoluble (mean loss, 54.2%), hemicellulose plus cellulose (mean loss, 40.6%) content and a relative increase of lignin content (mean gain, 34.4%). Among indicators of litter quality (C-to-N ratio, %N, %lignin, lignin-to-N ratio, HLQ), only some of them were correlated with litter decay. The best relationships were established between the decomposition rates (K,) and parameters integrating lignin contents (I = 0.997; n = 3; P < 0.01). The decomposition of l-y old litters fitted well with most of these parameters (0.999 < I < 0.997; n = 3; P < 0.01) in contrast to newly senescent litters
Keywords: Cellulose; decomposition; hemicellulose; leaf litter; Lignin; litter quality (voyant); mass loss; mineralization

Influence of leaf litter type on the chemical evolution of a soil parent material (sandstone) - Madeira, M; Ribeiro, C (Biogeochemistry, 1995)
The influence of leaves of Quercus suber L. and Eucalyptus globulus Labill. and needles of Pinuspinaster Ait. on a sandstone substrate was assessed through lysimetric studies during a ten-year period at a site in Central Portugal. The decomposition rate of Q. suber leaf litter was similar to that of E. globulus and higher than that of P pinaster needle litter. The proportion of nitrogen released from the Q. suber leaf litter was higher than that lost from the other organic species. Such a release was proportional to the initial nitrogen content in the substrates. The concentrations of both NHa-N and NO3-N were much higher in leachates collected under Q. suber leaf litter than in those collected under the other organic substrates. A similar trend was found in the leachates collected under the mineral substrate influenced by the studied organic substrates. The leachate concentrations of mineral N (especially NOs-N) were higher from the mineral substrate under Q. suber leaf litter than from this organic substrate itself. The mineral substrate under leaf litter of E. globulus or needle litter of P pinaster showed an increase in exchangeable base cations and pH values, and a decrease in extractable Al. Conversely, in the substrate with Q. suber leaf litter there was only a slight increase in exchangeable base cations and pH values, and a decrease in extractable Al. These results combined with those obtained in soils underE. globulus plantations indicate that changes found in these soils are due to soil and forest m
Keywords: decomposition rate; elemental fluxes; EUCALYPTUS; Leaching; leaf litter; Pinus pinaster; Quercus suber; soil chemistry